1989
DOI: 10.1104/pp.90.3.1029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Quantum Efficiencies of Photosystems I and II in Pea Leaves

Abstract: The irradiance dependence of the efficiencies of photosystems I and 11 were measured for two pea (Pisum sativum [L.]) varieties grown under cold conditions and one pea variety grown under warm conditions. The efficiencies of both photosystems declined with increasing irradiance for all plants, and the quantum efficiency of photosystem I electron transport was closely correlated with the quantum efficiency of photosystem 11 electron transport. In contrast to the consistent pattern shown by efficiency of the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 27 publications
5
101
0
1
Order By: Relevance
“…tion. As 4l declines qQ also declines; in previous studies (5,6) this relationship has been found to be curvilinear, however, in this instance the degree of scatter makes it impossible to determine the detail of the relationship between 4l and qQ. At values of X, close to 1.0 an abrupt decline of both qQ and X,, is implied because even at the lowest irradiance employed (120 ,umol m-2 s') qQ and oil are lower than the values recorded for the dark adapted state.…”
Section: Biophysical Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…tion. As 4l declines qQ also declines; in previous studies (5,6) this relationship has been found to be curvilinear, however, in this instance the degree of scatter makes it impossible to determine the detail of the relationship between 4l and qQ. At values of X, close to 1.0 an abrupt decline of both qQ and X,, is implied because even at the lowest irradiance employed (120 ,umol m-2 s') qQ and oil are lower than the values recorded for the dark adapted state.…”
Section: Biophysical Measurementsmentioning
confidence: 99%
“…Chl fluorescence and light-induced absorbance changes at 820 nm (AA820), due to P-700 oxidation or reduction, were measured within a leaf area of 1.25 cm2, defined by a circular mask as described previously (7,8 (6). The portion of the lamina that had been irradiated was immediately frozen and cut from the leaf using a solid brass cutter chilled to liquid nitrogen temperatures.…”
Section: Biophysical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the determination of CO 2 compensation points, CO 2 concentrations varied from 40 to 400 ppm. The maximum quantum yield of PSII (F v /F m ) was quantified according to Harbinson et al (1989) before and after shifting the plants to ambient air for 1 week (Timm et al, 2011).…”
Section: Gas Exchange and Chlorophyll Fluorescence Measurementsmentioning
confidence: 99%